(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
The article considers the provision of sustainable economic growth of regions in the world economy as an important factor of industrial transformation. This was explained by the fact that they conduct scientific research to strengthen the transformation processes in the industrial sector in the regions. The main directions of industrial transformation in the region are outlined.